The effectiveness of nirmatrelvir/ritonavir regimen in hospitalized renal transplant patients with prolonged COVID-19 infection: a multicenter clinical experience - Zhang, Huanxi; Wu, Wenrui; Zheng, Yitao; Fu, Qian; Chen, Peisong; Li, Jianyi; Wu, Zixuan; Gu, Jincui; Li, Jun; Liu, Longshan; Wu, Chenglin; Long, Sizhe; et al. (Renal failure, 2024)
Effectiveness of nirmatrelvir/ritonavir (NR) in kidney transplant recipients (KTRs) infected COVID-19 for more than 5 days has not been evaluated. In this multicenter retrospective study, 85 KTRs with COVID-19 were enrolled, including 50 moderate, 21 severe, and 14 critical patients. The median time from onset to starting NR treatment was 14 (IQR, 11-19) days. Before NR treatment, 96.5% patients reduced use of antimetabolites. They also stopped using calcineurin inhibitors (CNI) 12-24 hours before NR treatment, with CNI concentrations well-controlled during NR treatment. The use of intravenous corticosteroids increased with COVID-19 severity. The median time to reach viral negative conversion was 5 (IQR, 4-8) days for all patients. For moderate and severe COVID-19 patients, they had a low rate of ICU admission (1.4%), exacerbation requiring upgraded oxygen therapy (5.6%), and dialysis (2.8%); no intubation and mechanical ventilation, and no deaths were observed. Patients with critical COVID-19 had a low mortality rate (7.1%). A regimen including NR for clearing SARS-CoV-2 along with reducing immunosuppressants and using intravenous corticosteroids is associated with lower rates of exacerbation and mortality in KTRs who have moderate to critical SARS-CoV-2 infection and the virus still present after 5 days.